Psychometric proprieties analyses of Psychological Vulnerability Scale for secondary school students - Odete Araújo; Odete Araújo; Odete Araújo; Otília Freitas; Otília Freitas; Gilberta Sousa; Gilberta Sousa; Isilda Ribeiro; Isilda Ribeiro; José Carlos Carvalho; José Carlos Carvalho; Silvana Martins; et al. (Frontiers in Psychology)
BackgroundThe concept of psychological vulnerability is associated with the individual’s maladaptive cognitive beliefs, such as self-criticism, perfectionism, and the need for external validation and approval, reducing the individual’s ability to cope with negative life experiences. This study aimed to explore psychometric proprieties of the Psychological Vulnerability Scale in secondary school students.MethodsA psychometric study was conducted with a non-probabilistic sample of 1,875 secondary school students (55.5% female) aged 15 to over 18 years. Participants completed a self-report questionnaire that included demographic information, the Psychological Vulnerability Scale, and a Positive Mental Health questionnaire.ResultsAnalysis revealed acceptable skewness values (between −0.557 and 0.6385) and kurtosis (ranging from −1.29 to −0.704). Confirmatory factor analysis (CFA) indicated excellent global fit indices, confirming the original structure. Invariance testing between genders demonstrated that the Psychological Vulnerability Scale was consistent for boys and girls (configural invariance) and that each item contributed similarly to the construct (metric invariance). The Psychological Vulnerability Scale showed good internal consistency, with an ordinal Cronbach’s alfa above 0.70. Reliability estimates, including inter-item reliability or MacDonald’s Omega, indicated mean item-inter correlations falling within the recommended range of 0.15–0.50.ConclusionThe Psychological Vulnerability Scale is a reliable tool that plays a crucial role in promoting the mental health of secondary school students by providing a structured way to assess their emotional and psychological state. They not only help in the early identification of signs of stress, anxiety, or depression but also facilitate the development of personalized interventions, fostering a continuously supportive and healthy school environment.